2008
DOI: 10.1063/1.2939561
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen plasma and atomic oxygen treatments of diamond: Chemical versus morphological effects

Abstract: Effects and thermal stability of hydrogen microwave plasma treatment on tetrahedral amorphous carbon films by in situ ultraviolet photoelectron spectroscopy Chemical bonding and morphology of chemical vapor deposited diamond films were studied using high resolution electron energy loss spectroscopy and atomic force microscopy, following hydrogen plasma and atomic oxygen exposures. The hydrogen plasma exposure resulted in preferential etching of nondiamond carbon phases, selective etching of diamond facets, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…As can be seen, grains become more organized and smaller in size after plasma treatment. The effect of MW‐H plasma on the surface morphology of diamond films has been recently reported by our group 8. There we showed that hydrogen plasma selectively etches the non‐diamond carbon phase.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As can be seen, grains become more organized and smaller in size after plasma treatment. The effect of MW‐H plasma on the surface morphology of diamond films has been recently reported by our group 8. There we showed that hydrogen plasma selectively etches the non‐diamond carbon phase.…”
Section: Resultssupporting
confidence: 74%
“…Recently, several researches have shown that hydrogen plasma treatment improves the surface flatness and smoothes polishing scratches on diamond surfaces 1–11. Overall these studies show that exposure of diamond surfaces to hydrogen plasma at appropriate conditions may result in smoothing of these surfaces.…”
Section: Introductionmentioning
confidence: 67%
“…The hitherto reports on the impact of hydrogen treatment on the diamond layer surface structure have been inconsistent. On the one hand, Shpilman et al [ 26 ] have observed that the exposure of polycrystalline CVD diamonds to MW hydrogen plasma results in preferential etching of nondiamond carbon phases and formation of sp 3 -C–H - terminated surface. The authors of [ 23 ] have reported initial increase in the surface roughness with the time of plasma treatment but, for the longest time of hydrogen treatment application, they observed a decrease in this parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In the hot plasma zone, the oxygencontaining gas possibly evaporates and ionizes and then involves in CNPs formation resulting in more defect sites by oxygen atoms giving amorphous carbon. Meanwhile, as presented in this study, when toluene was used as medium in liquid arc discharge, only hydrogen plasma was supposedly involved, resulted in selective etching of carbon facets, and terminated as sp 3 −C−H species 53) .…”
Section: Identified Peaks Cnps-a Cnps-b Cnps-c Cnps-d 2ɵ (°) B (˚) D mentioning
confidence: 73%